Animal and human mucosal tissue models to study HIV biomedical interventions: can we predict success?. Issue 1 (2nd November 2015) - Dezzutti, Charlene S
Abstract : Introduction: Preclinical testing plays an integral role in the development of HIV prevention modalities. Several models are used including humanized mice, non‐human primates and human mucosal tissue cultures. Discussion: Pharmaceutical development traditionally uses preclinical models to evaluate product safety. The HIV prevention field has extended this paradigm to include models of efficacy, encompassing humanized mice, non‐human primates (typically Asian macaques) and human mucosal tissue (such as cervical and colorectal). As our understanding of the biology of HIV transmission improves and includes the influence of human behaviour/biology and co‐pathogens, these models have evolved as well to address more complex questions. These three models have demonstrated the effectiveness of systemic (oral) and topical use of antiretroviral drugs. Importantly, pharmacokinetic/pharmacodynamic relationships are being developed and linked to information gathered from human clinical trials. The models are incorporating co‐pathogens (bacterial and viral) and the effects of coitus (mucosal fluids) on drug distribution and efficacy. Humanized mice are being tailored in their immune reconstitution to better represent humans. Importantly, human mucosal tissue cultures are now being used in early clinical trials to provide information on product efficacy to more accurately characterize efficacious products to advance to larger clinical trials. While all of these models have made advancements in product development, each has limitations and the data need to be interpreted by keeping these limitations in mind. Conclusions: Development and refinement of each of these models has been an iterative process and linkages to data generated among each of them and from human clinical trials are needed to determine their reliability. Preclinical testing has evolved from simply identifying products that demonstrate efficacy prior to clinical trials to defining essential pharmacokinetic/pharmacodynamic relationships under a variety of conditions and has the potential to improve product selection prior to the initiation of large‐scale human clinical trials. The goal is to provide researchers with ample information to make conversant decisions that guide optimized and efficient product development.